Analysis of Dominant Risk Factors for Stroke Incidence and Unhealthy Lifestyle at Sidomulyo Pekanbaru Health Center - Chairil, Chairil (Advances In Social Humanities Research, 2024)
The introduction of health in the community is not only seen in the health sector but also must be seen in all sectors that influence health problems. Generally, there are two kinds of causes of stroke. The first is a blockage of the arteries, called ischemic stroke, while the second cause is rupture of blood vessels, or stroke ischemic, while the second cause is a rupture of blood vessels called a hemorrhagic stroke. Other causes of stroke can be a temporary disruption of blood flow to the brain, commonly referred to as an ischemic attack (TIA). These three conditions have a series of potential factors that trigger stroke. Hemorrhagic. Other causes of stroke can be a temporary disruption of blood flow to the brain, commonly referred to as an ischemic attack (TIA). These three conditions have a series of potential factors that trigger stroke. The study employed the Spearman rank correlation test method to investigate the relationship between smoking habits, alcohol consumption, lack of physical activity, and the occurrence of stroke. It involved 41 respondents from the Sidomulyo Health Center's jurisdiction. The findings revealed a significant association between smoking habits and stroke, as indicated by a significance value of 0.007, which is less than the threshold of 0.05. Similarly, there was a significant relationship observed between alcohol consumption and stroke, with a significance value of 0.016. However, the analysis showed no significant correlation between lack of physical activity and stroke, as the significance value of 0.446 exceeded the threshold of 0.05.